PENINGKATAN KETERAMPILAN ISTRI NELAYAN DALAM MENGELOLA JENIS IKAN EKONOMIS PENTING DALAM PEMBUATAN BAKSO IKAN DI DESA FALABISAHAYA, KECAMATAN MANGOLI UTARA - Firdaut Ismail; Ikbal Marus; Muhammad Irfan; Rovina Andriani; Fatma Muchdar (Jurnal Abdi Insani, 2023)
Concern to do more in helping people get out of extreme poverty and enjoy life through initiatives based on empowerment because of concern for the condition of people who are usually low-motivated as recipients of direct paths from poverty and low moral crises. Human Resources (HR). Providing knowledge and skills to the community to set up a business sector (home industry) that is acceptable and feasible to improve people's living standards is part of economic empowerment. Making fish balls is a business that can be run from home because Falabisahaya Village is known as a sea area because of the many islands and fish. This service activity aims to: 1) increase knowledge, insight and skills, fishermen's wives by providing training on fish processing-based products such as (Fish Meatballs), 2) providing motivation and entrepreneurial training so that fishermen's wives get provisions to strengthen their independent business , 3) providing training on packaging design and labeling of fish processing products, and providing business management training such as: selling price calculations, obtaining permits. The impact to be achieved is the creation of a community capable of managing existing resources and optimizing the potential of Falabisahaya Village. Data collection methods used are observation and interviews while the analytical method uses descriptive qualitative. The results that have been achieved with this program are increasing knowledge for fishermen's wives who are enthusiastic about training activities for making meatballs from tuna, as well as opening the insights of fishermen's wives that it turns out that tuna can be made into snacks such as meatballs/headballs which have very high nutritional value. high level and insight/knowledge about making meatballs from tuna fish, participants have also been able and able to design fishball product designs that are ready to be marketed.